2018
DOI: 10.1371/journal.pntd.0007021
|View full text |Cite
|
Sign up to set email alerts
|

Diisopropylphenyl-imidazole (DII): A new compound that exerts anthelmintic activity through novel molecular mechanisms

Abstract: Nematode parasites cause substantial morbidity to billions of people and considerable losses in livestock and food crops. The repertoire of effective anthelmintic compounds for treating these parasitoses is very limited, as drug development has been delayed for decades. Moreover, resistance has become a global concern in livestock parasites and is an emerging issue for human helminthiasis. Therefore, anthelmintics with novel mechanisms of action are urgently needed. Taking advantage of Caenorhabditis elegans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…3 G). The calculated IC 50 value of 13.8 μM ( Table 1 ) for LEV-induced paralysis compared favorably with concentration response data of former studies ( Qian et al, 2008 ; Sloan et al, 2015 ; Ding et al, 2017 ; Blanco et al, 2018 ; Risi et al, 2019 ). For example, Qian et al (2008) reported an IC 50 value for LEV of 9 μM in their motility assays, while a PDMS-microfluidic chip approach reported a lower IC 50 value of 2.2 μM ( Ding et al, 2017 ).…”
Section: Discussionsupporting
confidence: 64%
“…3 G). The calculated IC 50 value of 13.8 μM ( Table 1 ) for LEV-induced paralysis compared favorably with concentration response data of former studies ( Qian et al, 2008 ; Sloan et al, 2015 ; Ding et al, 2017 ; Blanco et al, 2018 ; Risi et al, 2019 ). For example, Qian et al (2008) reported an IC 50 value for LEV of 9 μM in their motility assays, while a PDMS-microfluidic chip approach reported a lower IC 50 value of 2.2 μM ( Ding et al, 2017 ).…”
Section: Discussionsupporting
confidence: 64%
“…Using C. elegans mutant and transgenic strains, we found that DII effects on adult nematodes rely on a previously unidentified UNC‐29‐containing muscle AChR, different from the classical Levamisole‐sensitive AChR. Interestingly, DII targets appear to be different between larvae and adults as unc ‐ 29 null mutant larvae are sensitive to the drug 66 . Summing up, using the model C. elegans we demonstrated that DII fulfills the major criteria necessary for the development of a novel anthelmintic, namely phylogenetic specificity and a novel biochemical mode of action.…”
Section: Relevant C Elegans Applications For Drug Target Discoveriesmentioning
confidence: 97%
“…Although this method has contributed to the elucidation of MOAs for several compounds previously proven to be biologically active, 137,138 the agar‐based technique does not permit large scale screenings because it is labor‐ and time‐consuming and needs large quantities of drugs 14 . Even with limitations, these assays are still very valuable for assessing small compound libraries 66 …”
Section: Elegans In Drug Discoverymentioning
confidence: 99%
See 2 more Smart Citations